GE_GERICHTE P/10064/2020 vom 10. Mai 2023 - GE Cour de justice (2023)
PORNOGRAPHIE DURE;FIXATION DE LA PEINE;TRAITEMENT AMBULATOIRE;SUSPENSION DE L'EXÉCUTION DE LA PEINE;CONFISCATION(DROIT PÉNAL) | CP.197.al5; CP.47; CP.42.al1; CP.44.al1; CP.51; CP.56; CP.63.al1; CP.63.al2; CP.69